2020
DOI: 10.4081/gc.2020.9137
|View full text |Cite
|
Sign up to set email alerts
|

Presbyphagia and dysphagia in old age

Abstract: Although presbyphagia is a clinically relevant problem among elderly population, possibly leading to dysphagia in old age, it remains a still underestimated health condition. The present review analyzes swallowing related anatomical and functional changes during aging, both in healthy people and in those affected by dysphagia. First of all, dysphagia in old people must not be confused with presbyphagia. To distinguish these two different conditions, a correct definition of both should be considered. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 65 publications
(77 reference statements)
0
18
0
Order By: Relevance
“…In addition, conditions such as Parkinson disease, myotonic dystrophy, and myasthenia gravis; infectious conditions such as candida; some connective tissue diseases; multiple comorbidities; multiple drug therapy (polypharmacy); and the use of swallowing-related drugs can cause both OPD and ED. 6 , 48 , 49 )…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, conditions such as Parkinson disease, myotonic dystrophy, and myasthenia gravis; infectious conditions such as candida; some connective tissue diseases; multiple comorbidities; multiple drug therapy (polypharmacy); and the use of swallowing-related drugs can cause both OPD and ED. 6 , 48 , 49 )…”
Section: Discussionmentioning
confidence: 99%
“…Almost all studies in older adults have reported changes in eating habits (reduced volume, changed consistency, and increased meal times) with increasing age. 6 , 38 , 48 , 52 ) Bolus formation and chewing ability especially decrease owing to age-related changes in swallowing function, in addition to changes in the choice of food consistency. 11 ) Therefore, we accepted that the symptom of changes in eating habits and difficulty with solid foods/liquids, especially in older adults, may be appropriate screening questions for the diagnosis of geriatric dysphagia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations